Implementasi Kajian Islam Dalam Pendidikan Dakwah Berbasis Tasawuf di Indonesia (Studi Analisis Pada Masyarakat Betawi) - Solahuddin, Solahuddin; Nuri Nurhaidah, Siti (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
This article examines the extent of the role of Sufism da'wah in improving the quality of faith of the Indonesian people, especially the Betawi community. Where the Betawi community experiences moral decadence, and with its geographical location, namely the Metropolitan City, the Betawi community is infected with a hedonistic and realistic lifestyle. This research is a field research. A sociological approach is used to analyze what Sufism looks like in the Betawi community in Indonesia. The theory used is the sociology of knowledge. This research focuses on da'wah as a center of study, and Sufism as an indicator in the formation of Betawi community morals. The results showed that forging life through Sufism da'wah produced good results in the Betawi community. Sufism da'wah in Indonesia as a medium of da'wah in Islamic Education aims to sharpen the heart and be forged with the application of Sufism teachings. So that problems are realized because of the preservation of reason.